THE EFFECT OF MAJOR METEOR STREAMS ON THE TOTAL OZONE IN THE EARTH’S ATMOSPHERE - Gorbanev, Yu. M.; Stogneeva, I. A.; Shestopalov, V. A.; Knyazkova, E. F.; Kimakovskaya, I. I.; Kimakovsky, S. R.; Golubaev, A. V. (Одеські астрономічні публікації, 2017)
The correlation between the total ozone and activity of major meteor streams, such as the Perseids, Geminids, Leonids and Orionids, has been found using the Total Ozone Mapping Spectrometer (TOMS) measurements of the global ozone distribution over the periods 1978 − 1993 and 1996 − 2001. The autocorrelation analysis of the total ozone time series for the period of about 20 years has conﬁrmed the existence of regular changes in the ozone levels at the peaks of meteor shower activity. It has been established that TO decreases after the dates of peak activity of meteor streams (e.g. the Perseids) or during the whole periods of meteor shower activity (e.g. the Geminids, Orionids and Leonids). The analysis of the total ozone distribution (in the Southern and Northern Hemispheres), as well as the local distribution of ozone (over the selected surface area of several hundred square kilometres), was performed during the Leonid meteor shower in 1999. The atmospheric zones for which the ozone distribution pattern can be described as a result of interaction between the meteor shower material and the ozone layer were localised by applying the TOMS data. Such zones correspond to the regions where the highest Leonid activity has been observed. According to the radar observations (conducted in Kazan, Russian Federation), three activity maxima of the 1988 Geminid shower were reported: on the nights of 7th, 12th and 14th December, 1988. The TO decrease was observed on the same dates. Thus, the analysis of the TO changes during the periods of intense meteor shower’s activity enables to preliminary assess the maximum overall decline in the total ozone concentration which makes about 5 DU over two weeks. From the results obtained it can be inferred that the ozone layer can be used as an indicator of the interaction between the meteoric material and the Earth’s atmosphere.